MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PAI DI SEKOLAH - anwar, Ahmad; Almurtaqi, Moch Ridwan (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
The problem of infrastructure becomes an obstacle in the learning process, especially in achieving quality and learning achievement. This research is qualitative descriptive research and library research. The data comes from various reading sources, book articles and other sources. The results of the research are: 1. Schools, in improving the quality of PAI learning, need educational facilities in the form of; chalk, markers, blackboards, blackboard erasers, tables, benches, chairs, cupboards, and educational media such as LCDs, cassettes, CDs, VCDs, and TVs. And the infrastructure needed includes; classrooms, libraries, prayer rooms and religious laboratories. PAI teacher. The process of managing educational facilities and infrastructure in schools is: planning procurement of goods, procurement of goods, procurement of facilities, maintenance, inventory, deletion, the process of deleting books that are obsolete and no longer relevant to the existing curriculum has never been carried out at all, books -Old books are still kept and neatly arranged.